Bioethanol production from Scenedesmus obliquus sugars: the influence of photobioreactors and culture conditions on biomass production - Miranda, J. R. (2013)
A closed-loop vertical tubular photobioreactor (PBR), specially designed to operate under conditions of scarce flat land availability and irregular solar irradiance conditions, was used to study the potential of Scenedesmus obliquus biomass/sugar production. The results obtained were compared to those from an open-raceway pond and a closed-bubble column. The influence of the type of light source and the regime (natural vs artificial and continuous vs light/dark cycles) on the growth of the microalga and the extent of the sugar accumulation was studied in both PBRs. The best type of reactor studied was a closed-loop PBR illuminated with natural light/dark cycles. In all the cases, the relationship between the nitrate depletion and the sugar accumulation was observed. The microalga Scenedesmus was cultivated for 53 days in a raceway pond (4,500 L) and accumulated a maximum sugar content of 29 % g/g. It was pre-treated for carrying out ethanol fermentation assays, and the highest ethanol concentration obtained in the hydrolysate fermented by Kluyveromyces marxianus was 11.7 g/L.